Research Note—Making Peer Review Evidence-Based: It's Time to Open the "Black Box". - Dunleavy, Daniel J. (Journal of Social Work Education)
Peer review serves an essential role in the cultivation, validation, and dissemination of social work scholarship. Nevertheless, the current peer review system has been described as unreliable, biased, ineffective, and unaccountable, among numerous other issues. That said, peer review is still commonly viewed as the best possible system of knowledge governance, given the relevant alternatives. In this research note, I scrutinize this assumption. Although peer review can sometimes be effective, it is not therefore a rigorous or even dependable system. Indeed, the practice of peer review in social work is overwhelmingly closed and opaque, and assurances of its rigor are speculative at best. After highlighting common criticisms of traditional peer review, I articulate a research agenda on "open peer review".